Safety of direct‐acting oral anticoagulants relative to warfarin in a matched cohort of liver transplant recipients. Issue 1 (12th December 2019) - Santeusanio, Andrew D.; Weinberg, Alan D.; Florman, Sander S.; Schiano, Thomas D.
Abstract: Despite increasingly widespread utilization of direct‐acting oral anticoagulants (DOACs), there remains limited experience with the use of these agents following liver transplantation. We performed a single‐center, retrospective review of liver transplant recipients prescribed DOACs or warfarin between January 2014 and January 2018. Patients receiving DOACs were matched with warfarin‐treated controls based on discrete clinical parameters and followed from the time of anticoagulant prescription, until treatment discontinuation or study conclusion. The primary endpoint for this review was the incidence of clinically relevant major or non‐major bleeding among the treatment groups. Twenty‐seven patients prescribed DOACs were identified for inclusion in the review, of which 20 could be matched with suitable warfarin controls. At the conclusion of the study, warfarin‐treated patients had a significantly higher incidence of clinically relevant bleeding (45% vs 15%; P  = .01). No statistically significant differences were found in the rate of new or recurrent thrombotic events. Multivariable logistic regression demonstrated that warfarin treatment was associated with a significantly higher odds of a bleeding event compared to treatment with a DOAC (OR = 6.9; 95% CI, 1.1‐44.6). DOAC use appears relatively safe compared with warfarin in select liver transplant recipients. Patient‐specific factors still bear consideration when selecting between the various anticoagulant options.